2007
DOI: 10.3168/jds.2007-0172
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Estradiol-17β Before the Last Gonadotropin-Releasing Hormone Injection of the Ovsynch Protocol in Lactating Dairy Cows

Abstract: The aim of this study was to determine whether an increase in circulating estrogen concentrations would increase percentage pregnant per artificial insemination (PP/AI) in a timed AI protocol in high-producing lactating dairy cows. We analyzed only cows having a synchronized ovulation to the last GnRH of the Ovsynch protocol (867/1,084). The control group (n = 420) received Ovsynch (GnRH--7 d--PGF(2alpha)--56 h--GnRH--16 h--timed AI). The treatment group (n = 447) had the same timed AI protocol with the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
143
8
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(178 citation statements)
references
References 47 publications
17
143
8
10
Order By: Relevance
“…This has been clearly shown in numerous studies using timed AI programs (Souza et al, 2007;Brusveen et al, 2008;Bisinotto et al, 2010b;Giordano et al, 2012b and. In addition, studies on cows that receive AI after detection of estrus, have generally reported that minor elevations in P4 near AI are also detrimental to fertility (De Silva et al, 1981;Waldmann et al, 2001;Ghanem et al, 2006), although some studies did not obtain this result (Erb et al, 1976;Plym Forshell et al, 1991).…”
Section: Pregnancy Loss In Dairy Cowsmentioning
confidence: 95%
See 4 more Smart Citations
“…This has been clearly shown in numerous studies using timed AI programs (Souza et al, 2007;Brusveen et al, 2008;Bisinotto et al, 2010b;Giordano et al, 2012b and. In addition, studies on cows that receive AI after detection of estrus, have generally reported that minor elevations in P4 near AI are also detrimental to fertility (De Silva et al, 1981;Waldmann et al, 2001;Ghanem et al, 2006), although some studies did not obtain this result (Erb et al, 1976;Plym Forshell et al, 1991).…”
Section: Pregnancy Loss In Dairy Cowsmentioning
confidence: 95%
“…In addition, studies on cows that receive AI after detection of estrus, have generally reported that minor elevations in P4 near AI are also detrimental to fertility (De Silva et al, 1981;Waldmann et al, 2001;Ghanem et al, 2006), although some studies did not obtain this result (Erb et al, 1976;Plym Forshell et al, 1991). During Ovsynch, the percentage of cows that do not have complete regression following the PGF2α treatment before timed AI has been reported to range from 5% to 30% (Moreira et al, 2000;Gumen et al, 2003;Souza et al, 2007;Brusveen et al, 2009;Martins et al, 2011b;Giordano et al, 2013b). A recent extensive study of incomplete luteolysis evaluated multiple blood samples in cows at first AI (n = 652) and second or greater AI (n = 394) (Martins et al, 2011b).…”
Section: Pregnancy Loss In Dairy Cowsmentioning
confidence: 99%
See 3 more Smart Citations